Determinação simultânea multiclasse de fármacos em água de consumo humano empregando extração em fase sólida e UHPLC-MS/MS - Oliveira, Júlia Antunes de (2019)
Pharmaceuticals are used in both human and veterinary medicine for the prevention and treatment of various diseases. The lack of adequate treatment for urban and industrial effluents associated with the incorrect disposal of unused or expired products results in the contamination of aquatic environments by pharmaceuticals and their metabolites. Unlike other contaminants, pharmaceuticals do not necessarily have to persist in the environment to cause harmful effects, because in addition to being released continuously, they are biologically active substances. The increase in consumption of medicines at a global level makes essential the study of the occurrence of these compounds in the aquatic environment. In this context, the development of reliable analytical methods is necessary to monitor the presence of pharmaceuticals in aqueous matrices potentially used for human supply. The objective of this work was to develop and validate a simple method for the simultaneous determination of pharmaceuticals of different classes in drinking water, using solid phase extraction (SPE) and ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS). Different sorbents, solvents and elution volumes were evaluated. The optimized conditions of the extraction step were: Strata™-X 200 mg/3 mL cartridge, sample with pH 5.5-6.0 with addition of 0.1% of EDTA, eluting solvent 1% (v/v) acetic acid in acetonitrile/metanol (1:1, v/v) and elution volume of 1 mL. The recovery results, evaluated at the levels 0.01, 0.02, 0.1, 0.4 and 1.0 μg L-1 (n=6), were between 70 and 119% with relative standard deviation (RSD) ≤19%. The limits of quantification and detection of the method were 0.01 to 0.1 μg L-1 and 0.003 to 0.03 μg L-1, respectively. The validated method was applied in 12 drinking water samples from different cities and regions of Rio Grande do Sul and the results indicated that three samples were contaminated with atenolol (0.026 μg L-1), carbamazepine (0.013 and 0.027 μg L-1) and paracetamol (0.016 μg L-1). The proposed method was considered adequate for the determination of 20 pharmaceuticals in drinking water and could be applied in routine analyzes due to its reliability and simplicity.